RESEARCH ON MILLING OF WEAK STIFFNESS PARTS BASED ON MAGNETORHEOLOGICAL FLUID AUXILIARY SUPPORT - ZHANG YongLiang; WANG KeYi; ZHANG ShuaiShuai (Jixie qiangdu, 2022)
According to the characteristics of the magnetorheological fluid, in this thesis, there are designs of a set of adaptive, flexible auxiliary supporting device units, which can be used to develop the processing accuracy of complex curved parts with weak rigidity. The magnetic field of the device is simulated by comsol using finite elements to determine its magnetic strength. It establishes the milling and positioning models of the workpieces with weak stiffness based on the magnetorheological effect, analyzing the positioning constraint models under the auxiliary support, calculating the deformation of the work pieces under static state, studying the influence of the device on the quality of the workpieces. It set up a milling test platform based on magnetorheological auxiliary support, milling parts with weak stiffness under the conditions of different current parameters, collecting acceleration signals for analysis by labview platform data acquisition system, measuring the surface roughness of the milling process. The results agree that, under the action of the magnetorheological auxiliary support, in comparison with the unsupported state, the vibration amplitude is reduced 46.9% to 75.7%, and the surface roughness of the workpieces with weak rigidity is about 69.89% to 80.61% lower.